The influence of longitudinal slope of main road carriage-way on the mass emission from road transport in the atmospheric air - Solukha, Igor (KNUCA, 2015)
Relevance: the issue of the impact of longitudinal slope of the street, as geometrical parameter of carriage-way, on mass emission of pollutants from motor transport is raised. The tasks of research: consider the concepts of longitudinal street slopes, discharge, exhaust gas, mass emission, atmospheric air. The technique of research: the theoretical technique of analysis for determining the role of longitudinal slope of a carriage-way on the adoption of engineering and planning decision of main roads intersection is implied. The results of research: the interdependence of the mass emission of pollutants into the atmospheric air from road transport and slope of a carriageway was established. Conclusions: It was established that with increasing slope mass emission of pollutants may grow 3...15 times as many.
Влияние продольного уклона проезжей части магистрали на массу выбросов от автомобильного транспорта в атмосферу
Keywords: longitudinal slope; mass emission; atmospheric air; продольный уклон; массы выбросов; атмосферный воздух